MARKETING STRATEGY ANALYSIS FOR FAST FOOD FRANCHISES - Muhamad Ali Murtado; Budi Prasetiyo (Media Inovasi Pendidikan dan Publikasi, 2023)
The purpose of this research is to examine the marketing strategy of PT. Hisana Fried Chicken, one of the fast food franchises in West Java. This study uses a qualitative case study methodology using Marketing Mix and SWOT Analysis. Data for cases was collected in various ways including narrative and personal interviews. This study expands the new packaging of marketing strategy and SWOT analysis for PT Hisana Fried Chicken to increase its competitive advantage. We only analyze the marketing strategy for the Margahayu Permai Branch, Bandung. The results of the research and discussion show that the Margahayu Hisana branch of fried chicken uses several processes in marketing strategy and product development such as conducting observations and interviews, observation results, alternative suggestions for improvement. In addition, a subsidiary of Margahayu Permai Hisana Fried Chicken implements its marketing strategy through STP (Segmentation, Targeting, Positioning) analysis. This study can provide more theoretical aspects to enrich knowledge in the field of management, especially in the field of marketing strategy. . This study examines Marketing Strategy Analysis combined with SWOT analysis in the Indonesian fast food franchise industry.